PRINCIPAL FUZZY IDEALS AND FILTERS ON A LATTICE - Benelbar, Khawla; Supervisor: Milles, Soheyb (University of m'sila, 2022)
,Ty AbR T wm ,TkbJ Abstract In this work, we generalize the notion of principal ideal (resp. filter) on a lattice to the setting of fuzzy sets and investigate their various characterizations and properties. More specifically, we show that any principal fuzzy ideal (resp. filter) coincides with a fuzzy down-set (resp. up-set) generated by a fuzzy singleton. Afterwards, for a given fuzzy set, we introduce two fuzzy sets : its fuzzy down-set and up-set, and we investiga
Keywords: sting properties. Key words : Lattice, fuzzy set, Principal fuzz